Persepsi masyarakat terhadap kepentingan seni persembahan kanak-kanak - Nur Amiza, binti Zainal Abidin (Universiti Malaysia Sarawak (UNIMAS), 2015)
The research is about public perceptions of the importance of children's performing arts in nation building. The objective of the study is to identify the perception of the general public of the importance of the performing arts in child development. This research aims to get people's views and those of interest mentality performing arts children. In addition, this study also was to determine the effects of children's performing arts to the formation of human capital through the eyes of the general public in developing children's performing arts. Using a combination of quantitative through the distribution of one hundred (100) questionnaires to the public involving children, youth and adults from urban and rural areas beyond the qualitative approach through interviews of a total of two (2) members of informers that involving teachers Sekolah Seni Kuching and observations were also made in this investigation. The findings obtained from the public perception and informers, performing arts prove the child is important in the development of the state of various aspects including human capital, economic and social.